Predictive power of objectivation of phimosis grade on outcomes of topical 0.1% betamethasone treatment of phimosis - Kühhas, Franklin; Tosev, Georgi (Urology, 2012)
Objective: To evaluate the predictive power of the objectivation of the phimosis grade according to the classification defined by Kikiros and Woodward, with regard to the expected efficacy of 0.1% betamethasone cream as a treatment option. Methods: From October 2010 to May 2011, a total of 55 boys (aged <10 years) were treated for phimosis at our department. An assessment of the category of phimosis and the retractability of the foreskin, according to the classification of Kikiros and Woodward, was performed. The proposed treatment options included complete circumcision or topical treatment with steroid cream (0.1% betamethasone-17-valerate). Results: Of the 55 patients, 19 (34.5%) underwent conventional circumcision, and 36 (65.5%) were treated with an 8-week course of topical steroid cream. The mean age was 3.9 years (range 0.6-10). Grade 1, 2, 3, 4, and 5 phimosis was seen in 1 (2.8%), 4 (11.1%), 8 (22.2%), 16 (44.4%), and 7 (19.4%) of the cases in the topical steroid cream group, respectively. The success rate for the topical steroid cream was 69.4% and 63.9% at 3 and 8.3 months, respectively. The objectivation of the phimosis grade did not predict the outcome (P > .05). No side effects were associated with the topical steroid treatment. Conclusion: The pretreatment classification of phimosis did not allow the prediction of success with the topical steroid treatment. We believe that topical steroid therapy with foreskin retraction and daily cleansing is a valid therapy modality that should be offered before any surgical intervention, regardless of the degree of phimosis.